Giant sacral chordoma. Diagnosis and treatment. - Lepera, Roberto; Lyford-Pike, Patrick; Salom, Andrés; Andreoli, Gustavo; Veirano, Gustavo (Cirugía del Uruguay, 2005)
The chordoma is a bony tumor, originating in ectoscopic remains of the notochordal tissue; its most frequent topography is found at sacra! leve!. lts diagnosis is general/y belated and the studies performed consist of images which are fundamental far its detection. Treatment is basical!y surgica/ and is performed by a multidisciplinary team. Radiotherapy is an adjuvant option. Local recurrence is the rule and constitutes main cause of death, with an overa/! survival at 5 years of50%.